Problematika Pendidik dalam Menyusun Modul Ajar pada Implementasi Kurikulum Merdeka di SD Negeri 4 Sesetan: Penelitian - Eksel Eka Brahmana; Ni Nyoman Mariani; Ni Kadek Supadmini (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to find out the problems of teachers in determining learning objectives in teaching modules, designing learning activities, designing learning media and designing assessments in teaching modules. The theories used are the theories of constructivism and behaviorism. The subject of this study are class teachers of SD Negeri 4 Sesetan. The data collection methods are structured interviews and document studies. The data that has been collected is analyzed by qualitative analysis method with steps of reduction, data presentation, and conclusion drawn. The results of the study show that (1) in determining the learning objectives of teachers face difficulties, namely, difficulties at the beginning of the implementation of the Merdeka Curriculum and difficulties in translating learning outcomes into learning objectives. (2) Teachers have difficulty choosing appropriate learning models and methods and vary learning activities when designing learning activities. (3) Teachers have difficulty choosing appropriate learning media and time constraints in designing learning media. (4) Teachers have difficulty designing a comprehensive assessment, namely measuring various aspects of students' abilities. Schools and teachers have tried to overcome this problem.